High levels of heat shock protein 70 are associated with pro-inflammatory cytokines and may differentiate early- from late-onset preeclampsia - Peraçoli, José Carlos [UNESP]; Bannwart-Castro, Camila F.; Romao, Mariana; Weel, Ingrid C.; Ribeiro, Vanessa R.; Borges, Vera Therezinha Medeiros [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Witkin, Steven Sol [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP] (Elsevier, 2013)
Preeclampsia (PE), a specific syndrome of pregnancy, can be classified into early and late onset, depending on whether clinical manifestations occur before or after 34 weeks' gestation. We determined whether plasma concentrations of Hsp60 and Hsp70 were related to circulating cytokine levels, as well as kidney and liver functions, in early- and late-onset PE. Two hundred and thirty-seven preeclamptic women (95 with early- and 142 with late-onset PE) were evaluated. Plasma levels of Hsp60, Hsp70, and their specific antibodies, tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1, IL-10, IL-12, and soluble TNF-α-receptor I (sTNFRI) concentrations, were determined by enzyme-linked immunosorbent assay (ELISA). Concentrations of Hsp70, TNF-α, IL-1β, IL-12, and sTNFRI were significantly elevated in patients with early-onset PE compared with women with late-onset PE; IL-10 levels were significantly lower in the early-onset PE group. Concentrations of urea, uric acid, proteinuria, glutamic oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), and lactate dehydrogenase (LDH) were also significantly higher in early-onset PE. The percentage of infants with intrauterine growth restriction was also significantly higher in women with early-onset PE. There were positive correlations between Hsp70 levels and TNF-α, TNFRI, IL-1β, IL-12, GOT, GPT, LDH, and uric acid concentrations in early-onset PE group. Thus, early-onset PE was associated with greater maternal and fetal impairment. There are differences in pathophysiology between early- and late-onset PE, highlighting by the difference in Hsp70 levels. © 2013 Elsevier B.V. All rights reserved.
Keywords: Cytokines; Hsp60; Hsp70; IUGR; Preeclampsia